Calcium-based composite heat storage material and preparation method thereof

By adding aluminum spinel-shaped materials to calcium-based heat storage materials, a uniformly dispersed structure is formed, which solves the problems of unstable performance and short cycle life of calcium-based heat storage materials, and achieves the efficient heat storage and heat exogenous properties of the materials promote.

CN116495762BActive Publication Date: 2025-02-18ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310277613.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-17
Publication Date
2025-02-18
Estimated Expiration
2043-03-17

AI Technical Summary

Technical Problem

Traditional calcium-based heat storage materials have problems such as unstable performance and short cycle life, which seriously restrict their development and application.

Method used

Add aluminum spinel-type materials to the calcium-based material, and form a uniformly dispersed structure on the surface of the calcium-based material through the aluminum spinel-type materials, preventing the agglomeration between calcium oxides and improving the resistance of calcium-based materials during high-temperature cycles Sintering capacity.

Benefits of technology

The circulating performance of calcium-based materials is improved, the high heat storage/exothermic density of calcium-based composite heat storage materials is ensured, and the service life of the material is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116495762B_ABST
    Figure CN116495762B_ABST
Patent Text Reader

Abstract

The present invention provides a calcium-based composite heat storage material and a preparation method thereof. The calcium-based composite heat storage material includes a calcium-based material and an aluminum spinel-type material, wherein the calcium-based material is calcium oxide or calcium carbonate. The preparation method includes a solid-phase doping method, in which the aluminum spinel-type material is prepared by a sol-gel method, and then the aluminum spinel-type material is mixed with calcium carbonate powder and heat-treated and carbonated to obtain a calcium-based composite heat storage material; or the calcium-based composite heat storage material is synthesized in one step by a sol-gel method. The composite heat storage material of the present invention utilizes the stability of the aluminum spinel-type material, and can effectively improve the problem of sintering failure of the calcium-based heat storage material. The preparation method of the present invention is simple, low-cost, and easy to operate, and while achieving high energy storage density, it improves the stability of the heat storage material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat storage materials, and in particular to a calcium-based composite heat storage material and a preparation method thereof. Background Art

[0002] Building a new power system with new energy as the main body has become a global consensus, and energy storage will participate as a core link. Since new energy power generation is volatile and random, it is impossible to adjust its own output to adapt to changes in user demand. The traditional "source follows load" model will no longer be applicable to the new power system. It is necessary to achieve a dynamic balance of power supply and demand through measures such as energy storage and rely on the coordinated interaction of source, grid, load and storage. Heat storage is an important part of the energy storage system.

[0003] Heat storage mainly includes three forms: sensible heat storage, latent heat storage and thermochemical heat storage. Sensible heat storage refers to the storage and release of heat by relying on the thermophysical properties of the heat storage material without chemical changes. In this process, only the temperature of the material itself changes. Sensible heat storage technology is mature and simple to operate. It is still one of the most widely used heat storage methods, but its heat storage density is relatively low. Phase change heat storage uses the absorption / release behavior of the material during phase change (such as solid-solid, solid-liquid, solid-gas, etc.) to store / release thermal energy. It has the advantages of high energy density and approximately constant temperature during the phase change process, but low thermal conductivity, and a single phase change material usually has insufficient performance and requires a complex packaging process. Thermochemical heat storage uses reversible thermochemical reactions to achieve the storage and release of thermal energy. The energy storage density of thermochemical heat storage materials is usually 0.5~3GJ / m 3 , which is about 8 to 10 times that of sensible heat materials and more than twice that of latent heat materials, and has low heat loss during long-term storage. Therefore, it is considered to be one of the most promising heat storage methods in the future.

[0004] Calcium-based thermal storage materials have high specific capacity, low specific mass and low preparation cost, and have been widely used in the field of energy storage. However, traditional calcium-based thermal storage materials have problems such as unstable performance and short cycle life, which seriously restrict their development and application. Summary of the invention

[0005] In view of the above problems, the present invention provides a calcium-based composite heat storage material and a preparation method thereof. By adding aluminum spinel-type material to the calcium-based material, the sintering resistance of the calcium-based material during high-temperature circulation is improved, thereby improving the circulation performance of the calcium-based material.

[0006] The invention provides a calcium-based composite heat storage material, comprising a calcium-based material and an aluminum spinel-type material, wherein the calcium-based material is calcium oxide or calcium carbonate.

[0007] Aluminum spinel material has excellent thermal stability and inertness, and aluminum has the function of promoting reaction and forming a skeleton. When the calcium-based material is undergoing a heat storage cycle, its carbonation degree will weaken as the sintering condition deepens. After being doped with aluminum spinel-type materials, the aluminum spinel-type materials form a uniformly dispersed structure on the surface of the calcium-based material, preventing the mutual agglomeration of calcium oxides, and can improve the sintering problem of calcium-based heat storage materials under high-temperature reaction conditions, thereby improving the cycle performance of calcium-based materials. In addition, the aluminum spinel-type material does not react with the material itself, which can avoid reducing the content of the main reaction substance (such as calcium carbonate) of the calcium-based composite heat storage material and damaging the reaction activity of calcium carbonate, thereby ensuring that the calcium-based composite heat storage material has a higher heat storage / heat release density.

[0008] In an optional technical solution of the present invention, the calcium-based composite heat storage material is calcium carbonate powder and aluminum spinel powder attached to the surface of the calcium carbonate powder.

[0009] According to the technical solution, the calcium-based composite heat storage material is in powder form. When the powdered calcium-based composite heat storage material is pressed to form a heat storage unit, it is beneficial to increase the density of the heat storage unit and improve the heat storage / release performance.

[0010] In an optional technical solution of the present invention, the aluminum spinel powder is uniformly dispersed and coated on the surface of the calcium carbonate powder.

[0011] According to the technical solution, the aluminum spinel material forms a uniformly dispersed structure on the surface of the calcium-based material, preventing the calcium oxides from agglomerating with each other. This can improve the sintering problem of the calcium-based heat storage material under high-temperature reaction conditions and improve the cycle performance of the calcium-based material.

[0012] In the optional technical solution of the present invention, the molecular formula of the aluminum spinel material is M x Al( 2x )O4, wherein M is one or more combinations of Mg, Ni, Fe, and Mn.

[0013] According to the technical solution, other metal elements are doped into the aluminum spinel type material, which can make it easy for the aluminum spinel type material to combine with calcium carbonate to form a skeleton structure. The skeleton structure can not only prevent the mutual agglomeration of calcium oxides, but also ensure the contact area between the calcium-based material and the air, thereby ensuring the heat storage / release effect.

[0014] In an optional technical solution of the present invention, the molar ratio of each component in the calcium-based composite heat storage material is Ca:M:Al=100:x:2x.

[0015] According to the technical solution, by controlling the molar ratio of each component in the calcium-based composite heat storage material within a reasonable range, the mass ratio of the calcium-based material to the spinel material can be controlled, which is beneficial for the aluminum spinel material to be dispersed and coated on the surface of the calcium-based material, thereby ensuring the contact area between the calcium-based material and the air.

[0016] In an optional technical solution of the present invention, the value range of x is 4-10.

[0017] According to the technical solution, by controlling the molar fractions of M and Al in the composite material within a specified range, the calcium-based material can be effectively blocked to avoid agglomeration and sintering of the calcium-based material under high-temperature reaction conditions. However, the higher the mass fraction of the aluminum spinel material, the lower the mass fraction of the calcium-based material. The main reaction substance of the calcium-based composite heat storage material is calcium carbonate. If the content of calcium carbonate is low, the energy density of the heat storage / heat release reaction of the material under the same mass conditions will be reduced. In addition, too many spinel-type carriers attached to the surface of calcium carbonate can easily cause insufficient contact reaction area between calcium carbonate and air. Therefore, when x in the aluminum spinel material is 4-10, the heat storage / heat release performance and cycle performance of the calcium-based composite heat storage material can be taken into account.

[0018] The present invention further provides a method for preparing the above-mentioned calcium-based composite heat storage material, comprising the following steps:

[0019] S1, pre-treating a certain proportion of solid calcium-based material and solid aluminum spinel-type material to obtain a mixed powder of the calcium-based material and the aluminum spinel-type material that is evenly mixed;

[0020] S2, calcining and carbonating the mixed powder formed in step S1 at high temperature, and finally cooling to obtain a calcium-based composite heat storage material.

[0021] The present invention uses a solid-phase doping method to synthesize the calcium-based composite heat storage material, which has low cost and short time consumption. The prepared samples are uniform and small in size, and the preparation process is relatively simple.

[0022] In an optional technical solution of the present invention, the solid aluminum spinel material is prepared by a sol-gel method.

[0023] According to this technical solution, compared with natural aluminum spinel ore, the preparation of solid aluminum spinel material by sol-gel method is beneficial to ensure the proportion of each element in the aluminum spinel material, reduce impurities, and ensure the thermal stability and inertness of the aluminum spinel material in the calcium-based composite heat storage material.

[0024] In an optional technical solution of the present invention, the pretreatment includes mixing the calcium-based material with the aluminum spinel-type material, and then crushing, screening and ball milling.

[0025] According to the technical solution, pre-treating the calcium-based material and the aluminum spinel material is beneficial to increasing the uniformity of the powder.

[0026] The present invention further provides a method for preparing the above-mentioned calcium-based composite heat storage material, comprising the following steps:

[0027] V1, stirring and dissolving a certain proportion of nitrate of calcium-based material and nitrate corresponding to aluminum spinel material and citric acid into deionized water to form a mixed solution;

[0028] V2, adding a certain proportion of ethylene glycol to the mixed solution obtained in step V1 and stirring evenly to obtain a gel solution;

[0029] V3, drying, calcining, carbonating and cooling the gel solution obtained in step V2 to obtain a calcium-based composite heat storage material.

[0030] When the present invention adopts the sol-gel method to prepare the calcium-based composite heat storage material, the raw materials used are first dispersed in a solvent to form a low-viscosity mixed solution. Therefore, the raw materials used to prepare the calcium-based composite heat storage material can obtain uniformity at the molecular level in a relatively short time. When forming a gel, the raw materials can be uniformly mixed at the molecular level. The prepared calcium-based composite heat storage material has good uniformity, high purity and fine powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic flow chart of the method for preparing the calcium-based composite heat storage material in the first embodiment of the present invention.

[0032] Figure 2 This is a schematic flow chart of a method for preparing a calcium-based composite heat storage material in a second embodiment of the present invention.

[0033] Figure 3 Schematic diagram of X-ray diffraction analysis of the calcium-based composite heat storage material in an embodiment of the present invention.

[0034] Figure 4 This is a schematic diagram of thermogravimetric curves of multiple cycle reactions of the calcium-based composite heat storage material in an embodiment of the present invention. DETAILED DESCRIPTION

[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] [First embodiment]

[0037] The invention provides a calcium-based composite heat storage material, comprising a calcium-based material and an aluminum spinel-type material, wherein the calcium-based material is calcium oxide or calcium carbonate.

[0038] Aluminum spinel materials have stable crystal form, firm structure, high melting point, and stable chemical properties. Therefore, under high-temperature reaction conditions, they have excellent thermal stability and inertness, do not react with the material itself, and can avoid reducing the content of the main reaction substance (such as calcium carbonate) of the calcium-based composite heat storage material and damaging the reaction activity of calcium carbonate, ensuring that the calcium-based composite heat storage material has a higher heat storage / heat release density. When the calcium-based material is undergoing a heat storage cycle, its carbonation degree will weaken as the sintering condition deepens. After being doped with aluminum spinel materials, since aluminum has the function of promoting reaction and forming a skeleton, the aluminum spinel material is easy to form a uniformly dispersed structure on the surface of the calcium-based material, preventing the mutual agglomeration of calcium oxide, and can improve the sintering problem of the calcium-based heat storage material under high-temperature reaction conditions, thereby improving the cycle performance of the calcium-based material. In addition, there is a strong interaction between the aluminum spinel material and calcium carbonate, so that the aluminum spinel material can be attached / coated on the surface of calcium carbonate and is not easy to fall off during multiple heat storage / heat release cycle reactions.

[0039] In a preferred embodiment of the present invention, the calcium-based composite heat storage material is calcium carbonate powder and aluminum spinel powder attached to / coated on the surface of the calcium carbonate powder.

[0040] Through the above method, the calcium-based composite heat storage material is in powder form. By pressing the powdered calcium-based composite heat storage material into a heat storage unit, it is beneficial to increase the density of the heat storage unit and improve the heat storage / release performance; and the powdered calcium-based composite heat storage material can reduce space occupancy when stored.

[0041] In a preferred embodiment of the present invention, the aluminum spinel powder is uniformly dispersed and coated on the surface of the calcium carbonate powder. The uniformity can prevent local agglomeration on the surface of the calcium-based material, and the dispersion can ensure a reasonable contact area between the calcium carbonate and the air, thereby ensuring the heat storage and release performance of the calcium-based composite heat storage material.

[0042] Through the above method, the aluminum spinel material forms a uniformly dispersed structure on the surface of the calcium-based material, preventing the mutual agglomeration of calcium oxides, improving the sintering problem of the calcium-based heat storage material under high-temperature reaction conditions, and achieving the improvement of the cycle performance of the calcium-based material.

[0043] In a preferred embodiment of the present invention, the molecular formula of the aluminum spinel material is M x Al( 2x)O4, wherein M is one or more combinations of Mg, Ni, Fe, and Mn. The aluminum spinel type material is doped with a variety of metal elements, which can make it easy for the aluminum spinel type material to combine with calcium carbonate to form a stable skeleton structure. The skeleton structure can prevent the mutual agglomeration of calcium oxides and ensure the contact area between the calcium-based material and the air, thereby ensuring the heat storage / release effect.

[0044] In a preferred embodiment of the present invention, the molar ratio of each component in the calcium-based composite heat storage material is Ca: M: Al = 100: x: 2x. By controlling the molar ratio of each component in the calcium-based composite heat storage material within a reasonable range, the mass ratio of the calcium-based material to the spinel material can be controlled, which is conducive to the dispersion and coating of the aluminum spinel type material on the surface of the calcium-based material, thereby ensuring the contact area between the calcium-based material and the air.

[0045] In a preferred embodiment of the present invention, the value range of x is 4-10. By controlling the molar fractions of M and Al in the composite material within the specified range, the calcium-based material can be effectively blocked to avoid the agglomeration and sintering of the calcium-based material under high-temperature reaction conditions. However, the higher the mass fraction of the aluminum spinel material, the lower the mass fraction of the calcium-based material. The main reaction substance of the calcium-based composite heat storage material is calcium carbonate. If the content of calcium carbonate is low, the energy density of the heat storage / heat release reaction of the material under the same mass conditions is reduced. In addition, too much aluminum spinel material adheres to the surface of calcium carbonate, which easily causes insufficient contact reaction area between calcium carbonate and air. Therefore, when x in the aluminum spinel material is 4-10, it can effectively block the contact between calcium carbonate without basically affecting the reaction area of ​​calcium carbonate contacting with air, avoid agglomeration and sintering of calcium-based materials under high-temperature reaction conditions, improve the reaction degree and cyclic reaction performance of the calcium-based composite heat storage material in the heat storage / heat release reaction, and take into account the higher heat release density of the calcium-based composite heat storage material.

[0046] like Figure 1 As shown, for the above calcium-based composite heat storage material, the present invention further provides a method for preparing the above calcium-based composite heat storage material, comprising the following steps:

[0047] S1, pre-treating a certain proportion of solid calcium-based material and solid aluminum spinel-type material to obtain a mixed powder of the calcium-based material and the aluminum spinel-type material that is evenly mixed;

[0048] S2, calcining and carbonating the mixed powder formed in step S1 at high temperature, and finally cooling to obtain a calcium-based composite heat storage material.

[0049] The calcium carbonate of the present invention is fully mixed with the aluminum spinel material in a molar fraction ratio, and then the mixed powder is compounded by high-temperature calcination. This preparation method has the advantages of low cost, high output, short time consumption, simple equipment and preparation process, high production efficiency, etc., is suitable for large-scale industrial production, and the prepared samples are uniform and small in size. Specifically, the aluminum spinel material and calcium carbonate are weighed and mixed according to the corresponding mass of the corresponding molar ratio, and then ball milled for 60 minutes with a ball mill, and then the aluminum spinel material and calcium carbonate solid powder after being fully mixed are placed in a tubular furnace with a heating rate of 10°C / min, maintained at 800°C, calcined for 1 hour, then cooled to 700°C, switched to a carbon dioxide atmosphere, and carbonated for 1 hour. Finally, after waiting to cool to room temperature, the calcined composite material is taken out, and a calcium-based composite heat storage material formed by the aluminum spinel material and calcium carbonate is obtained, wherein the spinel carrier particles are uniformly attached to the surface of the calcium carbonate particles.

[0050] In a preferred embodiment of the present invention, the solid aluminum spinel material is prepared by a sol-gel method.

[0051] The aluminum spinel material is prepared by the sol-gel method. The sol-gel method is to uniformly mix the raw materials in the liquid phase, and perform hydrolysis and condensation chemical reactions to form a stable transparent sol system in the solution. After aging, the sol particles slowly polymerize to form a gel. The gel is dried, sintered and solidified to prepare a nanostructured material. The sol-gel method can achieve molecular level uniformity in a relatively short period of time, thereby preparing a composite material with high purity and good crystallization.

[0052] Specifically, the steps of preparing aluminum spinel material by sol-gel method are as follows:

[0053] First, weigh the aluminum spinel raw materials (magnesium nitrate and aluminum nitrate in a molar ratio of 1:2; or nickel nitrate and aluminum nitrate), citric acid and ethylene glycol respectively;

[0054] Then all the nitrates and citric acid were dissolved in an appropriate amount of deionized water and stirred at 70°C for 3 hours under a magnetic stirrer;

[0055] Then, ethylene glycol was added, and stirring was continued at 90° C. for 2 hours using a magnetic stirrer.

[0056] After the stirring is completed, the raw materials are taken out and placed in a blast drying oven with the temperature of the drying oven set to 200° C. for a drying time of 3 hours.

[0057] After drying, the raw material was placed in a tube furnace with a heating rate of 10°C / min, first calcined at 450°C for 4 hours, and then calcined at 800°C for 4 hours. Finally, after cooling to room temperature, it was taken out and ground into powder to obtain a solid powdery aluminum spinel material.

[0058] Preferably, the aluminum spinel raw material (magnesium nitrate and aluminum nitrate in a molar ratio of 1:2; or nickel nitrate and aluminum nitrate), citric acid and ethylene glycol are weighed according to a molar ratio of 3:3:2. This ratio can reduce the amount of citric acid and ethylene glycol while ensuring a high purity of the prepared sample.

[0059] Preferably, the chemical reagents such as magnesium nitrate, aluminum nitrate (or nickel nitrate, aluminum nitrate), citric acid and ethylene glycol in the raw materials for preparing the aluminum spinel type material are of analytical purity, high purity and few interfering impurities. This can minimize the impact of impurities on the heat storage / heat release chemical reaction of the calcium-based composite heat storage material, and avoid damaging the heat storage / heat release reaction characteristics and cycle performance of the heat storage material.

[0060] The spinel carrier obtained by the sol-gel method has high purity, good crystallinity, small particle size and uniform particle size. The uniformly mixed powdered calcium carbonate and aluminum spinel material undergo high-temperature calcination and carbonation, and the aluminum spinel material powder can be evenly attached to the surface of calcium carbonate, thereby effectively preventing calcium oxide from agglomerating and sintering under high-temperature reaction conditions, and a calcium-based composite heat storage material with excellent cyclic heat storage / heat release performance can be obtained.

[0061] In a preferred embodiment of the present invention, the pretreatment includes mixing the calcium-based material with the aluminum spinel material, and then crushing, screening and ball milling. In the above manner, by pretreating the calcium-based material and the aluminum spinel material, it is beneficial to increase the uniformity and fineness of the powder.

[0062] like Figure 3 The figure shows a schematic diagram of X-ray diffraction analysis of the calcium-based composite heat storage material in an embodiment of the present invention. The aluminum spinel material is preferably a combination of one or more of MgAl2O4 or NiAl2O4 or FeAl2O4 or MnAl2O4. The complexes formed by different aluminum spinel materials MgAl2O4 or NiAl2O4 or FeAl2O4 or MnAl2O4 and calcium carbonate will not produce new phases, indicating that the aluminum spinel material can always remain alone under the high temperature reaction conditions of the heat storage / heat release reaction, and will not react with the calcium carbonate particles to form new substances, thereby avoiding reducing the content of the main reaction substance (calcium carbonate) of the calcium-based composite heat storage material and damaging the reaction activity of calcium carbonate, thereby ensuring that the calcium-based heat storage material has a higher heat storage / heat release density.

[0063] like Figure 4 The figure shows a schematic diagram of thermogravimetric curves of multiple cyclic reactions of the calcium-based composite heat storage material in an embodiment of the present invention. The calcium-based composite heat storage material composed of calcium carbonate and a spinel-type carrier provided by the present invention has a high degree of reaction in multiple heat storage / heat release cycles, that is, the calcium-based composite heat storage material provided by the present invention has excellent cyclic reaction performance.

[0064] [Second embodiment]

[0065] See also Figure 2 As shown, for the above calcium-based composite heat storage material, the present invention further provides a method for preparing the above calcium-based composite heat storage material, comprising the following steps:

[0066] V1, stirring and dissolving a certain proportion of nitrate of calcium-based material and nitrate corresponding to aluminum spinel material and citric acid into deionized water to form a mixed solution;

[0067] V2, adding a certain proportion of ethylene glycol to the mixed solution obtained in step V1 and stirring evenly to obtain a gel solution;

[0068] V3, drying, calcining, carbonating and cooling the gel solution obtained in step V2 to obtain a calcium-based composite heat storage material.

[0069] When the present invention adopts the sol-gel method to prepare the calcium-based composite heat storage material, the raw materials used are first dispersed in a solvent to form a low-viscosity mixed solution. Therefore, the raw materials used to prepare the calcium-based composite heat storage material can obtain uniformity at the molecular level in a relatively short time. When forming a gel, the raw materials can be uniformly mixed at the molecular level. The prepared calcium-based composite heat storage material has good uniformity, high purity and fine powder.

[0070] Specifically, the raw materials required for preparing calcium-based composite heat storage materials by the sol-gel method include calcium nitrate, aluminum nitrate, magnesium nitrate (or aluminum nitrate, nickel nitrate), ethylene glycol and citric acid. The preparation method mainly includes the following steps:

[0071] Providing calcium nitrate, magnesium nitrate, aluminum nitrate (or calcium nitrate, nickel nitrate, aluminum nitrate) in a molar ratio of 100:6:12 as main raw materials;

[0072] The main raw materials, ethylene glycol, and citric acid were mixed in a molar ratio of 3:3:2, and deionized water was added to prepare the composite calcium-based thermal storage material Ca by the sol-gel method. 100 (MgAl2O4)6, which is similar to the method of preparing aluminum spinel material by sol-gel method, and will not be described in detail here;

[0073] Specifically, when preparing the main raw materials, calcium nitrate, magnesium nitrate and aluminum nitrate are fully mixed in a molar ratio of 100:6:12 to achieve uniform doping of calcium, magnesium and aluminum elements at the molecular level in preparation for subsequent reactions.

[0074] Preparation of Ca 100 (MgAl2O4)6, the composite heat storage material Ca was prepared by sol-gel method. 100 The basic principle of (MgAl2O4)6 is: dissolve metal nitrate and citric acid in a solvent, use citric acid as a chelating agent to form a complex with metal ions, add ethylene glycol for polymerization, and then generate a complex gel through a sol-gel process at a certain temperature. Finally, a composite calcium-based heat storage material is obtained through drying, calcination, and carbonation.

[0075] The sol-gel method has many unique advantages compared to other methods: since the raw materials used in the sol-gel method are first dispersed into a solvent to form a low-viscosity mixed solution, the mixing of the raw materials can obtain uniformity at the molecular level in a relatively short time, and the raw materials can be uniformly mixed at the molecular level when forming a gel. Since the solution reaction step is passed, it is easy to evenly and quantitatively incorporate some trace elements to achieve uniform doping at the molecular level. Compared with solid-phase reactions, chemical reactions are easier to carry out and only require lower synthesis temperatures. It is generally believed that the diffusion of components in the sol-gel system is in the nanometer range, while the diffusion of components in solid-phase reactions is in the micrometer range, so the reaction is easy to carry out and the temperature is lower.

[0076] Specifically, in this embodiment, the main raw materials (calcium nitrate, magnesium nitrate, aluminum nitrate (or nickel nitrate, aluminum nitrate) in a molar ratio of 100:6:12), ethylene glycol, and citric acid are first weighed according to a molar ratio of 3:3:2, and then calcium nitrate, magnesium nitrate, aluminum nitrate, citric acid and an appropriate amount of deionized water are added to a beaker, and stirred at a constant temperature of 70°C for 2 hours with a magnetic stirrer, and then the previously weighed ethylene glycol is added, and the magnetic stirrer is continued to stir at a constant temperature of 90°C for 2 hours. After two stirrings, the raw materials are taken out and placed in a blast drying oven, the drying oven temperature is set to 200°C, and the drying time is 3 hours. After drying, the raw materials are placed in a tubular furnace with a heating rate of 10°C / min, first maintained at 450°C, calcined for 2 hours, and then maintained at 800°C, calcined for 1 hour, and then maintained at 700°C in a carbon dioxide atmosphere, and carbonated for 1 hour. Finally, after waiting to cool to room temperature, it is taken out and ground into powder to obtain a composite calcium-based heat storage material Ca 100 (MgAl2O4)6.

[0077] Compared with the prior art, the calcium-based composite heat storage material provided by the present invention overcomes the problem of the traditional calcium-based heat storage material having a decreased heat storage cycle performance under multiple high-temperature environments. The preparation method provided by the present invention can make the aluminum spinel material powder with uniform particle size uniformly coated on the surface of calcium carbonate, and have a strong interaction with calcium carbonate, and can be firmly and stably attached during the cyclic reaction of the calcium-based composite heat storage material. In addition, the aluminum spinel material does not react with calcium carbonate, avoiding the reduction of heat storage / heat release energy density and the loss of reaction performance, which can not only effectively solve the problem of agglomeration and sintering, but also ensure excellent cyclic reaction characteristics.

[0078] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a calcium-based composite heat storage material, characterized in that: The following steps are involved: V1, stirring and dissolving nitrate and citric acid into deionized water to form a mixed solution, wherein the nitrate includes calcium nitrate salt corresponding to the calcium-based material and the aluminum spinel type material M x Al( 2x )O4 corresponding to the nitrate M salt and the aluminum nitrate salt, M is one or more combinations of Ni, Fe, Mn; the molar ratio between the calcium nitrate salt, the nitrate M salt and the aluminum nitrate salt is calcium nitrate salt: nitrate M salt: aluminum nitrate salt = 100:x:2x, and the value range of x is 4-10; V2, adding a certain proportion of ethylene glycol to the mixed solution obtained in step V1 and stirring evenly to obtain a gel solution, wherein the molar ratio of nitrate:ethylene glycol:citric acid is 3:3:2; V3, drying, calcining, carbonating and cooling the gel solution obtained in step V2 to obtain the calcium-based composite heat storage material.

2. The method for preparing the calcium-based composite heat storage material according to claim 1, characterized in that: The calcium-based composite heat storage material is calcium carbonate powder and aluminum spinel powder attached to the surface of the calcium carbonate powder.

3. The method for preparing the calcium-based composite heat storage material according to claim 2, characterized in that: The aluminum spinel powder is uniformly dispersed and coated on the surface of the calcium carbonate powder.

4. The method for preparing the calcium-based composite heat storage material according to claim 1, characterized in that: The aluminum spinel material is prepared by a sol-gel method.